The Impact COVID-19 Pandemic on Productivity of Tax Return Document Processing in the New Normal Era at Tax Data and Document Processing Center - Pri Budiarti Rini Sejati (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to determine the impact of the Covid-19 Pandemic on the productivity of  documents in the New Normal Era at PPDDP. This type of research is a descriptive study, with a research focused by analyzing the production of Tax Return document processing before and after the Covid-19 pandemic. The Purpose of this scientific article is to provide a new view to the State Civil Service (SCS) that the normal era is a pushing factor or triger for future organizational management innovation.